Lapnana, a new genus of tribe Evacanthini (Hemiptera: Cicadellidae: Evacanthinae) from India - Jat, Monica; Meshram, Naresh M.; Dey, Debjani (Zootaxa, 2022)
A new leafhopper genus Lapnana gen. nov. and species Lapnana ishanya, sp. nov. are described and illustrated from Arunachal Pradesh, India. The new genus is closely related to genus Onukindia Viraktamath and Webb but differs in having a median lamellate carina extending from the base to apex of the crown and ventral processes on the male pygofer.